The current state and prospects of using biogas as an energy carrier for stationary and transport applications - Biernat, Krzysztof; Różnicka, Izabela (Studia Ecologiae et Bioethicae, 2012)
Both governmental and international programs support the promotion of biofuels and aim to increase the limit of renewable energy used in the fuel energy balance. Biogas is produced during the anaerobic methane fermentation process and it is known as a significant source of renewable energy, contributing to agriculture and environmental protection. Three types of biogas can be distinguished: biogas from sewage sludge, biogas collected from land`fils, and agricultural biogas. There are several possibilities of using upgraded biogas. Biogas can be used in cogeneration systems to provide heat and electricity, in transportation as a motor fuel and in the production of biohydrogen. Biogas upgrading process leads to a product which is characterized by the same parameters as compressed natural gas. Direct biogas use in the production of hydrogen is possible because of prior purification from traces like hydrogen sulfide, except carbon dioxide, by which the reaction can proceed in the desired manner.